Regional differences in the influence of the North Atlantic Oscillation on seasonal river runoff in Poland - Wrzesiński, Dariusz (Quaestiones Geographicae, 2011)
In this paper, an analysis of monthly and seasonal runoff volumes in two stages of the North Atlantic Oscillation are presented. The analysis embraced runoff at 146 profiles located on 96 Polish rivers during the years 1951-2000. The changes in the runoff conditions of Polish rivers in the two NAO stages and their spatial diversity were determined based on the differences between runoff observed in the years of exceptionally high (NAODJFM > 2,0) and low (NAODJFM < -2,0) values of the winter NAO index. The results of the research indicate that the influence of the North Atlantic Oscillation on the runoff of Polish rivers is diverse in terms of time and space. A classification of rivers was made in terms of the similarity of deviations of their seasonal runoff between the different NAODJFM stages. In the classification procedure use was made of Ward's method of hierarchical grouping. In this way, five classes of the river profiles under analysis were obtained. Environmental conditions in the catchments and hydrological regime features clearly influence the regional differences in the impact of the North Atlantic Oscillation on the flow of rivers.